Effect of Trunk Exercises on Spastic Cerebral Palsy Children's to improve Sitting Postural Control - Nida Javed, Shoaib Waqas, Muhammad Tariq, Tehmina Malik, Hassan Bin Akram, Mehwish Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cerebral palsy is a neurological disorder of brain, which impacts on posture, balance, and motor skills of a child due to in coordination between nervous and musculoskeletal system. Aim: To improve functional independence among children with spastic cerebral palsy, so that independent sitting could be achieved, by which quality of life of these children, labor of therapist and caregiver was minimized. Methods: The study comprised a total of 29 diagnosed individuals with spastic palsy from the Ghurki Trust and Teaching Hospital. Those who fulfill the inclusion criteria were examined by the pediatric department in GTTH. By using randomized sampling method the subjects were assigned to perform the task. Pre-operative and post-operative assessment was made on group to assess the percentage of gross motor skill by using GMFM Score Sheet. Patients were engaged into series of physical rehabilitation program based on trunk control and strengthening exercises. Results: The finding of the study showed that 6.9 % kids were in age group 13 months to 18 months, 44.8 % were in between 19 months to 24 months of age, 31% between 25 months to 30 months, and 17.2 % between age group of 31 months to 36 months. The mean difference is 11.93 between pre and post treatment, had Standard deviation 4.11. P value is less than 0.05 which indicates that intervention is significant. Conclusion: It is concluded that trunk exercises improve sitting postural control among Spastic Cerebral Palsy children. Key words: CP, GMFCS, GMFM, Trunk Exercise, Spastic CP